ANALISIS IMPLEMENTASI PERATURAN PEMERINTAH NOMOR 39 TAHUN 2018 TENTANG KEPROTOKOLAN PADA BAGIAN PROTOKOL DAN KOMUNIKASI PIMPINAN SEKRETARIAT DAERAH KABUPATEN LAMPUNG BARAT - Asmaria Asmaria; M. Fikri Akbar; Imam Sumantri (Universitas Bandar Lampung (UBL), 2020)
The implementation of Government Regulation Number 39 Year 2018 regarding Protocols in the Protocol and Communication Section of Leaders is still not going well, this is because there are still many protocol staff who do not understand the rules of the Protocol itself and are still based on existing customs. That can be an obstacle in the service of protocol in the Protocol and Communication Section of the Head of the Regional Secretariat of West Lampung Regency. The research approach uses a qualitative descriptive approach. The results showed that the implementation of Government Regulation Number 39 Year 2018 on Protocol in the Protocol and Communication Section of the Head of the Regional Secretariat of West Lampung Regency was still not going well because of the inhibiting factors, namely inadequate Human Resources in the field of protocols as well as facilities and infrastructure tasks. protocol that has not yet fulfilled capacity.